Editors with multiple retractions, but who serve on journal editorial boards: Case studies - Teixeira da Silva, Jaime Α.; Vuong, Quan-Hoang (Epistēmēs Metron Logos, 2023)
In a recent opinion paper (https://doi.org/10.3897/ese.2022.e95926), it was argued that individuals with multiple retractions or a record of academic misconduct should not serve as editors, including as editors- in-chief, on the editorial boards of scholarly or academic journals. As a first step towards appreciating how such a policy could be applied in practice, the presence of 30 individuals listed on the Retraction Watch Leaderboard on editorial boards was screened. Six cases are highlighted to gain an appreciation of the potential reputational risks that journals and publishers might incur by including individuals with a tainted academic record on editorial boards. Given the reputational, legal and other risks associated with this type of assessment and decision, more formal positioning and guidance are needed by global ethics policy-related bodies such as COPE, the ICMJE, and the CSE, even more so in journals that claim to follow these organizations’ ethical guidelines.